2010
DOI: 10.1002/pro.557
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization reveals that a PilZ domain protein undergoes substantial conformational change upon binding to cyclic dimeric guanosine monophosphate

Abstract: PA4608 is a single PilZ domain protein from Pseudomonas aeruginosa that binds to cyclic dimeric guanosine monophosphate (c-di-GMP). Although the monomeric structure of unbound PA4608 has been studied in detail, the molecular details of c-di-GMP binding to this protein are still uncharacterized. Hence, we determined the solution structure of c-di-GMP bound PA4608. We found that PA4608 undergoes conformational changes to expose the c-di-GMP binding site by ejection of the C-terminal 3 10 helix. A dislocation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Several X-ray and nuclear magnetic resonance (NMR) structures of the PilZ domain receptors have now been solved (50,82,83,150,151). These studies have confirmed the bioinformatic (48) and biochemical (52) prediction that two short stretches of residues comprising the PilZ domain consensus, RxxxRx 20 -30 (D/ N)x(S/A)xxG, are involved in c-di-GMP binding ( Fig.…”
Section: Types Of C-di-gmp Receptorsmentioning
confidence: 57%
“…Several X-ray and nuclear magnetic resonance (NMR) structures of the PilZ domain receptors have now been solved (50,82,83,150,151). These studies have confirmed the bioinformatic (48) and biochemical (52) prediction that two short stretches of residues comprising the PilZ domain consensus, RxxxRx 20 -30 (D/ N)x(S/A)xxG, are involved in c-di-GMP binding ( Fig.…”
Section: Types Of C-di-gmp Receptorsmentioning
confidence: 57%
“…PP4397 from Pseudomonas putida binds two molecules of c-di-GMP and undergoes a dimer-to-monomer transition (Ko et al 2010). PA4608 from P. aeruginosa is a single-domain-containing protein that binds to one molecule of c-di-GMP and undergoes rearrangement to expose a negative surface of the protein that is predicted to function in downstream processes (Habazettl et al 2011, Shin et al 2011). These differences in stoichiometry and oligomeric states are predicted to allow for diverse forms of c-di-GMP-dependent regulation (Habazettl et al 2011, Ko et al 2010, Shin et al 2011).…”
Section: C-di-gmp Effector Systemsmentioning
confidence: 99%
“…Most members of this family have a conserved motif, RxxxR-D/NxSxxG (1). Conserved residues in this motif are proposed to be critical in interacting with the c-di-GMP ligand, according to the recently published X-ray crystal structures of PlzD and PA4608, two PilZ domain proteins from V. cholerae and P. aeruginosa, respectively (4,21,48).…”
mentioning
confidence: 99%